2017
DOI: 10.2298/hemind160318030w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 24-epibrassinolide on seedling growth and distribution of mineral elements in two maize hybrids

Abstract: In this study, influence of wide range of 24-epibrassinolide (24-EBL) on early growth potential of two maize hybrids (ZP 434 and ZP 704) was examined. Paper concerns germination, seedling biomass, important chlorophylls content, and redistribution of elements (heavy metals and microelements), in a seedlings of the maize hybrids, as influenced by different 24-EBL concentrations. It was found that hybrids react differently to exogenously applied hormone. The biggest differences between two examined maize hybrids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The same reports (Waisi et al, 2015a;Waisi, 2017a) revealed that BRs contribute to an irregular distribution of different classes of polyphenols in seedlings as the water-soluble polyphenols primarily occur in the radicle, while lipophyllic polyphenols are primarily associated with the plumule, which may affect the tolerance of maize seedlings to unfavourable environmental conditions during their early vegetative growth. Besides, the effects of BRs on redistribution of micronutrients and heavy metals in maize seedling organs were also analyzed, and a conclusion was made that they prevent their uptake and translocation to key organs (plumule and radicle) of young maize plants, which indicates that these phytohormones may be adequately used in recultivation processes in technogenically degraded soils (Waisi et al, 2017a). The used methods are explained in detail by Waisi (2016) and Waisi et al (2015aWaisi et al ( , 2017aWaisi et al ( , 2017b.…”
Section: Treatment Of Maize Seeds and Seedlings With Brassinosteroidsmentioning
confidence: 85%
See 3 more Smart Citations
“…The same reports (Waisi et al, 2015a;Waisi, 2017a) revealed that BRs contribute to an irregular distribution of different classes of polyphenols in seedlings as the water-soluble polyphenols primarily occur in the radicle, while lipophyllic polyphenols are primarily associated with the plumule, which may affect the tolerance of maize seedlings to unfavourable environmental conditions during their early vegetative growth. Besides, the effects of BRs on redistribution of micronutrients and heavy metals in maize seedling organs were also analyzed, and a conclusion was made that they prevent their uptake and translocation to key organs (plumule and radicle) of young maize plants, which indicates that these phytohormones may be adequately used in recultivation processes in technogenically degraded soils (Waisi et al, 2017a). The used methods are explained in detail by Waisi (2016) and Waisi et al (2015aWaisi et al ( , 2017aWaisi et al ( , 2017b.…”
Section: Treatment Of Maize Seeds and Seedlings With Brassinosteroidsmentioning
confidence: 85%
“…We believe that lower 24-EBL concentrations speed up biochemical and metabolic processes in the plumule and radicle of maize seedlings, which grow fast (attention to germination), while seedlings did not suffer from osmotic stress (low trehalose). The effect of BRs on germination and early vegetative growth of maize seedlings was also analyzed and an interesting correlation was revealed in the altered metabolism of sugars and polyphenols under the influence of BRs, which corresponds with high vigour of maize seedlings (Waisi et al, 2015a;Waisi et al, 2017a). The same reports (Waisi et al, 2015a;Waisi, 2017a) revealed that BRs contribute to an irregular distribution of different classes of polyphenols in seedlings as the water-soluble polyphenols primarily occur in the radicle, while lipophyllic polyphenols are primarily associated with the plumule, which may affect the tolerance of maize seedlings to unfavourable environmental conditions during their early vegetative growth.…”
Section: Treatment Of Maize Seeds and Seedlings With Brassinosteroidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, 24-EBL enhances the uptake of K + , Ca 2+ , and Mg 2+ in the roots, and these cations are preferentially transported to younger leaves through vascular tissues to reduce Cd translocation [ 17 ]. Moreover, 24-EBL enhances the absorption of essential inorganic ions, reducesthe uptake of toxic ions, and promotes ion homeostasis, especially K + /Na + , Ca 2+ , and Mg 2+ in the upper leaves, Ca 2+/ Na + and Mg 2+ /Na + in the roots, and K + /Na + in the petioles [ 2 , 123 ]. Hence, the co-application of Si+EBL reduced Cd accumulation by maintaining ion homeostasis, offering better conditions for osmotic adjustment, and blocked Cd uptake by co-precipitation.…”
Section: Discussionmentioning
confidence: 99%